Clinical features and comorbidity in very early-onset schizophrenia: a systematic review - Di Luzio, Michelangelo; Pontillo, Maria; Villa, Marianna; Attardi, Anna Gaia; Bellantoni, Domenica; Di Vincenzo, Cristina; Vicari, Stefano (Frontiers in Psychiatry, 2023)
Background Very early-onset schizophrenia (VEOS) is a form of schizophrenia that manifests before the age of 13 years and is characterized by the presence of positive, negative, and disorganized symptoms. The condition is exceptionally rare and, to date, limited studies have been conducted, resulting in incomplete information about its clinical features. Methods The present study involves a systematic review of the existing literature regarding the clinical features and comorbidities of VEOS. Results The first search retrieved 384 studies. Of these, 366 were removed following the application of exclusion criteria, resulting in 18 studies for the final set. Conclusion The results highlight that VEOS shares similarities with early-onset and adult-onset schizophrenia but also exhibits distinct and recognizable characteristics, including a more severe clinical profile (particularly in females), increased visual hallucinations, and high comorbidities with neurodevelopmental disorders. These findings may support clinicians in formulating early diagnoses and developing effective treatment strategies for pediatric and adolescent patients with psychosis.